IDENTIFIKASI LOKASI, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN(STUDI KASUS PADA KONSUMEN AYAM GEPREK 69 CABANG SUKORAME) - Ogha, Mellynia (Universitas Nusantara PGRI Kediri, 2022)
Business in Indonesia is currently very diverse, especially in the culinary field. Because of this, a business actor must always innovate his products in order to be able to compete and attract the attention of consumers. Because one of the goals of business actors is to improve a purchasing decision. The purpose of this study was to analyze whether the location, price and promotion variables were able to influence purchasing decisions at Ayam Geprek 69 Sukorame Branch. The technique in this study uses a causal relationship research with a sample of 40 which is then analyzed using classical assumption testing, multiple linear regression analysis, coefficient of determination and hypothesis testing using SPSS v.25 software. The results of this study indicate that there is an insignificant effect between location and promotion, there is a significant effect of price. And there is a simultaneous influence between location, price, and promotion